Investigating Boron Isotopes for Identifying Nitrogen Sources Supplied by Submarine Groundwater Discharge to Coastal Waters - Tamborski, Joseph; Brown, Caitlin; Bokuniewicz, Henry; Cochran, J. K.; Rasbury, E. T. (Frontiers in Environmental Science, 2020)
Stable isotopes of oxygen, nitrogen and boron were used to identify the sources of NO3- in submarine groundwater discharge into a large estuary (Long Island Sound, NY). Potential contaminants such as manure, septic waste and fertilizer overlap in 15N and18O but have been shown to have distinctive 11B in non-coastal settings. Two sites on the north shore of Long Island (NY) were studied with different, up-gradient land use, representative of mixed medium-density residential housing and agriculture. These sites have overlapping 15N and18O measurements in nitrate. Boron isotopes and concentrations are measurably different between the two sites, with little overlap. There is little correlation between 11B and [B] or salinity, demonstrating that direct mixing relationships between the fresh groundwater and seawater are unlikely to account for the variability, although the groundwater mixtures appear to have a seawater origin. Well water and rain water samples show a range of 11B that can explain the high values of the submarine groundwater samples. Potential nitrate endmembers, including septic system samples, fertilizers and a manure sample were also analyzed for 11B to compare to two sites with fresh submarine groundwater discharge up to 75 cm d-1that delivers significant NO3- to this coastal area. Several interesting conclusions emerge from this survey. One is that seawater provides boron but not salinity to fresh groundwaters collected within the subterranean estuary. This is likely through sea spray and boric acid volatilization. Another is that the large range of 11B with no trend in [B] suggests multiple N (and B) sources, consistent with our working knowledge that submarine groundwater discharge brings diffuse, non-point sourced contaminants to Long Island Sound.